Análise comparativa do desempenho de filtros de potência passivo e ativo para mitigação de distorções harmônicas em um precipitador eletrostático - Mendes, Poliana Rockenbach (2021)
The automation of industrial processes brings with it the appearance of harmonic distortion in the electrical system, since such automation is obtained through the use of semiconductor devices, resulting in insertion of non-linear loads in the electrical power distribution system. This distortion can cause energy losses destined for the Brazilian Interconnected System (SIN), due to the abundant presence of harmonic distortion in the auxiliary services of a power plant, which impacts the company's earnings and profits. In general, harmonic distortions should be mitigated only when they exceed standardized limits, and the ideal time to analyze mitigation strategies is during the design of new facilities or the purchase of new equipment that will be inserted into the system. Currently, there are several harmonic mitigation solutions, but they cannot be used in a generalized way, which brings the need for a specific study for each case. Among the most used options to mitigate harmonics is the insertion of power filters in the power system, whose main objective is to reduce the amplitude of currents of one or more harmonic frequencies. This paper presents the design, modeling and simulation of four tuned passive shunt power filters and one active shunt power filter. The simulation of the insertion of these filters in the common connection point of the electrostatic precipitator of auxiliary services in a Thermal Power Plant, is done in the ATP Draw® software, for the passive filters and in MATLAB® for the active filter. It was chosen to implement the single-tuned band-pass filters in parallel for the three highest harmonics found in the system (orders 2, 4 and 8), in order to analyze the performance of the topology regarding the mitigation of these distortions. For the active filter, the VSI inverter topology with three legs was chosen, using the dq theory to obtain the reference currents. The benefit of using a passive filter to mitigate order 2 and 4 harmonics in this system is evident, taking into account that the complexity and cost of the project are low, however, the active filter topology is considered as the best result for the correction of current harmonic distortions in this point, the active filter topology was chosen as the best result for distortion correction. current harmonics at this point, as it causes less energy impact on the system.